Gender differences in reading skills in english: a case study of 11th grade public school students in UAE - Maryam AlSereidi, Ali Salem (Technium Social Sciences Journal, 2021)
This study aims to examine gender differences in reading skills (literal, inferential, critical, and appreciative) of 11th Grade students in public high schools in UAE and determine to what extent they are statistically significant. The survey uses a quantitative questionnaire about reading skills (literal, inferential, critical, and appreciative) in English. A total of 600 students (n = 300 male, n = 300 female) participated in this survey. A one-way ANOVA test is employed for data analysis. The results indicate that female students obtain higher mean scores (M = 3.54, SD =1.08) for reading practices with lower-level thinking skills (literal reading) and experience inferential and critical reading practices more than male students. However, they exhibit no significant difference in reading practices with lower-level thinking skills and inferential, critical, and appreciative reading skills in English. Future studies could extend this research domain to other countries in the Middle East with large student samples.